Prevalence and phylogenic study of human T-lymphotropic virus 1 in patients with thalassemia in the northeast of Iran. (May 2017) - Abedi, Farshid; Mozhgani, Sayed-Hamidreza; Rahimzadegan, Marzieh; Gudarzi, Hoda; Valizadeh, Narges; Rezaee, Seyed Abdolrahim
Aim: This study aimed to investigate the frequency and phylogenetic distribution of human T-lymphotropic virus type 1 (HTLV-1) in thalassemia cases.Methods: Between 2006 and 2013, a total of 100 thalassemic individuals were investigated for HTLV-1 infections.Results: Four people (4%) were reactive for HTLV antibodies. No considerable correlation was seen between factors such as age, blood transfusion history, surgery, marital status, gender and blood types. All HTLV-1 sequences belonged to the transcontinental (A) subgroup in the cosmopolitan (a) subtype.Conclusion: In addition to phylogenetic distribution, our results demonstrate that the prevalence of HTLV-1 infection among thalassemia patients in Mashhad is higher than that of previous studies.